DAERAH RISIKO COVID-19 DI KABUPATEN BADUNG - Made Agus Sugianto (Jurnal Kesehatan Medika Udayana, 2020)
ABSTRACTBackground: The report of the Covid-19 Task Force in Badung Regency shows an increasing trend of Covid-19 cases in Badung Regency from March to August 2020.Purpose: the purpose of this study is to obtain a map of the Covid-19 risk areas in the Badung Regency. Methods: the method in this study is a descriptive-analytic with a cross-sectional study design. This research was conducted in Badung Regency for two months from 15 July to 15 September 2020 using secondary data from the daily reports of the Covid-19 Task Force in Badung Regency from 23 August 2020 to 23 September 2020. Results: the results of the zoning mapping from the Epidemiological aspect showed that 4 sub-districts (66.6%) of the 6 sub-districts were the Covid-19 red zones. From the aspect of Regional Capability in Handling Cases of Covid-19 Infection, it shows that all districts are included in the High Response category in handling Covid-19, and from the aspect of Regional Ability to Trace the History of Close Contact of People Infected with Covid-19 it appears that 3 districts (50%) are included in the category of areas with moderate ability, while the other 3 sub-districts are included in the category of regions with low ability. Conclusion: Based on the results of this study, it is concluded that the level of the spread of Covid-19 in the Badung Regency is very high, even though the level of readiness of the Government in handling Covid-19 cases is very good. The geography of the area bordering other districts/ cities and high population mobility are suspected to be the triggers for the high number of Covid-19 cases.Keywords: Mapping; Covid-19; Badung Regency ABSTRAKLatar belakang: laporan Satuan Tugas Covid-19 Kabupaten Badung menunjukan tren peningkatan kasus Covid-19 di Kabupaten Badung dari bulan Maret hingga Agustus 2020. Tujuan: tujuan penelitian ini adalah untuk memperoleh gambaran peta daerah risiko Covid-19 di Kabupaten Badung. Metode: metode dalam penelitian ini adalah descriptive analytic dengan desain crosssectional Study. Penelitian ini dilaksanakan di Kabupaten Badung selama dua bulan dari tanggal 15 Juli sampai dengan 15 September 2020 dengan menggunakan data sekunder laporan harian Satuan Tugas Covid-19 Kabupaten Badung dari tanggal 23 Agustus 2020 sampai dengan 23 September 2020. Hasil: hasil pemetaan daerah dari aspek Epidemiologi menunjukan sebanyak 4 kecamatan (66,6%) dari 6 kecamatan merupakan zona merah Covid-19. Dari aspek Kemampuan Daerah Dalam Menangani Kasus Infeksi Covid-19 menunjukan bahwa semua kecamatan masuk dalam kategori Respon Tinggi dalam penanganan Covid-19 dan dari aspek Kemampuan Daerah Dalam Melakukan Penelusuran Riwayat Kontak Dekat Orang Yang Terinfeksi Covid-19 nampak bahwa 3 kecamatan (50%) masuk dalam kategori Daerah Dengan Kemampuan Sedang, sedangkan 3 kecamatan lainnya masuk dalam kategori Daerah Dengan Kemampuan Rendah. Simpulan: berdasarkan hasil penelitian tersebut disimpulkan bahwa tingkat persebaran Covid-19 di Kabupaten Badung sangat tinggi, meskipun tingkat kesiapan Pemerintah dalam menangani kasus Covid-19 sangat bagus. Geografis daerah yang berbatasan dengan kabupaten/kota lain serta tingginya mobilitas penduduk di duga sebagai pemicu tingginya kasus Covid-19.Keywords: Pemetaan; Covid-19; Kabupaten Badung